2022
DOI: 10.29333/iji.2022.15445a
|View full text |Cite
|
Sign up to set email alerts
|

Higher Order Thinking Skills Achievement for Biology Education Students in Case-Based Biochemistry Learning

Abstract: The development of HOTS has become a new trend in the 21st century learning process. Many approaches and models are applied in the learning process to achieve HOTS, including case-based learning approaches. This study aims to reveal a description of the level of student HOTS achievement in Case-Based Biochemistry Learning which took place in the Even Semester of 2019/2020. This research is descriptive research. A sample of 24 people was taken from students of the Biology Education Department, Faculty of Teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In science learning, it was also found that learning emphasizes mastery of a number of facts and concepts and does not facilitate students to have comprehensive learning outcomes (Çam & Geban, 2017;Mardiani et al, 2022;Wikanta & Susilo, 2022). The outcome of learning tends to be limited to mastery of concepts without the ability to higher order thinking & (Pratiwi, Rahayu, & Fajaroh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In science learning, it was also found that learning emphasizes mastery of a number of facts and concepts and does not facilitate students to have comprehensive learning outcomes (Çam & Geban, 2017;Mardiani et al, 2022;Wikanta & Susilo, 2022). The outcome of learning tends to be limited to mastery of concepts without the ability to higher order thinking & (Pratiwi, Rahayu, & Fajaroh, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Students must understand, analyze each other, categorize, manipulate, create new ways creatively, and apply them in finding solutions to new problems (Jaenudin et al, 2020). The low level of high-level thinking skills (HOTS) was stated by Wikanta et al (2022) who stated that the problems that occur in schools are that the questions or questions used in cognitive assessments tend to test more on the memory aspect, while for questions that train higher order thinking skills (HOTS) tend to be absent. A teacher in training students to work on questions characterized by high level thinking (HOTS) can develop an assessment instrument based on high level thinking (HOTS).…”
Section: Introductionmentioning
confidence: 99%
“…The goal of teaching mathematics is no longer merely developing the skills of performing arithmetic operations, or solving abstract problems that are not related to reality without links between them and this reality according to the traditional view (Kilpatrick, 2020;Al-Nofli, 2022). Rather, the goal of mathematics education has become to provide learners with thinking and correct understanding, including developing their abilities to solve the problems they face in their environment (Birgili, 2015;Wikanta & Susilo, 2022). The educational literature agrees on the importance of the teacher's role in teaching, and that it is the ruling factor in the success or failure of the teaching and learning processes (Lawrence & Tar, 2018), as the teacher's competence depends to a large extent on his knowledge and skills in teaching, and the question became: "What makes someone a good teacher?"…”
Section: Introductionmentioning
confidence: 99%